Review of the Chinese Megahyliota Thomas, 2004 (Coleoptera: Silvanidae: Brontinae), with description of a new species - Liu, Zhen-Hua; Li, Zhi-Qiang (Zootaxa, 2026)
Three species of the genus Megahyliota Thomas are recorded from the southwest of China, with description of a new species, Megahyliota angustus sp. nov. from Mêdog, Xizang; Megahyliota feae (Grouvelle, 1892) is newly recorded from China and redescribed. Megahyliota cryptolucidus is firstly recorded from Yunnan. Illustrations of the habitus and diagnostic characters are provided, with a key to species of the genus.